PENDIDIKAN MULTIKULTURAL DALAM KONSEPSI FILSAFAT PENDIDIKAN ISLAM - B, Muhaemin; Hasyim, Abdul Wahid (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2022)
This paper discusses Multicultural Education in the Philosophy of Islamic Education. The purpose of this study is to give us an understanding of multicultural education which is a concept, idea, or philosophy as a set of beliefs and explanations that recognize and assess the importance of cultural and ethnic diversity in shape the lifestyle, social experience, personal identity, educational opportunities of individuals, groups, and countries. Such multicultural education is very urgent to be implemented in educational practice. This is because education with a multicultural perspective is believed to be able to grow and develop students to become individuals who are not only proud of themselves (the culture, language, and other specialties they have), but are also able to recognize, accept, respect the different specialties that other people have. ready to live in harmony. Multicultural education has conceptual relations and relevance to Islamic religious doctrine